Oxidative Stress in Patients With Acne Vulgaris - Ozer Arican; Ergul Belge Kurutas; Sezai Sasmaz (Hindawi Limited, 2005)
Acne vulgaris is one of the common dermatological diseases and its pathogenesis is multifactorial. In this study, we aim to determine the effects of oxidative stress in acne vulgaris. Forty-three consecutive acne patients and 46 controls were enrolled. The parameters of oxidative stress such as catalase (CAT), glucose-6-phosphate dehydrogenase (G6PD), superoxide dismutase (SOD), and malondialdehyde (MDA) in the venous blood of cases were measured spectrophotometrically. The values compared with control group, the relation between the severity and distribution of acne, and the correlation of each enzyme level were researched. CAT and G6PD levels in patients were found to be statistically decreased, and SOD and MDA levels were found to be statistically increased (P<.001). However, any statistical difference and correlation could not be found between the severity and distribution of lesions and the mean levels of enzymes. In addition, we found that each enzyme is correlated with one another. Our findings show that oxidative stress exists in the acne patients. It will be useful to apply at least one antioxidant featured drug along with the combined acne treatment.